Decomposition of dyes in the textile wastewater with ozone - Koyuncu, I; Afsar, H (MARCEL DEKKER INC, 1996)
Ozone treatment of textile wastewater and recycling of this treated water as process water have been investigated. Effects of pH,temperature,dye concentration and UV radiotion on the treatment of some azo dyes such as N-ROT-GRE, N-ORANGE and INDISOL-RUBINOL with ozone were investigated. Temperature was found not to effect the decomposition rates of these dyes. The ozone treatment was found to be more ecomomical with the diluted dye solution than with concentrated solutions. No positive effect of UV radiotion on decomposition of dyes were observed. When the flow rate of ozone was 0.2 mg/sec. chemical oxygen demand (COD) decreases of 44 mg and 36.6 mg per minute were found for the wastewaters of cotton dying and wool dying respectively.
Keywords: ozone; textile wastewater; treatment; dye; AZO DYES; OZONATION; Engineering; Environmental Sciences & Ecology